SOWING ILLUSIONS, REAPING DISARRAY: MEDIA INFLUENCE, URBAN MIGRATION, AND THE DISMANTLING OF SOCIETAL NORMS IN SOUTH ASIA - Siddiqui, Hassan Rasheed; Muniza, Maria (The journal of contemporary issues in business and government, 2009)
It aimed at a comprehensive understanding and practical application of information technology with respect to urban migration and the breakdown of values and norms of South Asian digital media. This page is intentionally left blank Media as social- Central to social- how we collectively construct, update and propagate ideals of: Ideally, success, when we can experience enclosure by diegesis, media will share a portion of the audience with social- media platforms, and With presenting and potencier expressions of ideologies. These narratives are also often glorifying the values of materialism, emotional alienation and socio-cultural oppobrium and creating new intersecting lines of interest from vogue on the streets, while simultaneously imbibing a sense of ennui, creating an angst and dislocation of consciousness that unifies in confusion strata of youth. The finding demonstrates how deeply embedded media has become — in some cases, an informal education system at least as powerful as family or school in shaping behavior and aspirations in ways that threaten indigenous cultural identities. There are few overarching governmental regulations on what can be shown online, nor is there much protection for vulnerable elements of the population or encouragement for values-based programming. These and other groups are underrepresented or ignored in popular narratives that paint broader groups (e.g., women, children, persons with disabilities) as victims of the violence. These are momentous findings and they call on policymakers, educators, media producers and civil society to concerted actions that will mitigate the negative impact of digital content and nurture endemic values. It will take strong regulatory initiatives, inclusive representation, and educational outreach on the part of the public to steer the media landscape in emerging nations toward peace, kindness, and sustainable development so that they can plant the seeds of social stability instead of mirages and unrest.